(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Differential equations is one of the oldest field in the modern mathematics. It is consider being the mathematics of applications in the fields of engineering, physics, life sciences and other areas in the field of mathematical modeling. Differential equations is a higher mathematics course of applications. This needs the prior knowledge of calculus as foundation for this course. This material is an introduction to ordinary differential equations. This covers the basic topics on ordinary differential equations that can serve as foundations in advanced studies in differential equations.